Enhancing the Operational Efficiency of Marine Vessel Main Engine Systems through Cost Reduction via Reliability Techniques - Carter, Alexander; Lee, Fiona; Taylor, Benjamin (Ayden Journal of Engineering and Applied Sciences, 2024)
This research seeks to use reliability technique to improve operational output through cost reduction of the main engine system of a ship. The various subsystems of the marine vessel main engine were identified. The failure mode effect and criticality index of the engine system and their root causes were analyzed. The reliability of the main engine system was analyzed using exponential reliability model and a maintenance task that reduces the operational cost of main engine system was generated thereby improving output. The reliability centred maintenance technique identified all the perspectives of failures in the ship main engine systems and employed the appropriate maintenance approach for each failure respectively. The results of the reliability analysis performed on the main engine systems generated the proposed preventive maintenance (PM) tasks and plan. Decrease in the rate of Run-ToFailure (RTF) data remains inevitable and programmed performance of condition based, task demand and fault finding (CD, TD and FF) was recommended. The projected work program if implemented will decrease labour cost from N177, 600,000.00/year to N100, 800,000.00/year (approximately 43.24% of the total annual labour expenditure). The projected PM scheduling outcomes showed a 44.64% saving in the total cost of maintenance when compared with the existing RTF practice. The main engine systems reliability increases with decreased labour cost. The proposed spare parts plan for the main engine systems was generated and the results showed that approximately 55.42% of the yearly costs of spare parts are saved when projected PM scheduling is adopted